16Sr RNA Gene and reca Gene as Taxonomic Tool for Detection of Burkholderia Cepacia Isolated from Patients from Baghdad / Iraq - Zahraa Kareem Raheem (Journal of Global Pharma Technology, 2018)
Twenty two isolates of Burkholderia cepatia (B. cepacia) were isolated from clinical sources and  diagnostic using VITEK 2 system and GNB ID cards. Two molecular diagnostic methods have been used to confirm the identification., the first method is the polymerase chain reaction (PCR) by 16S rRNA gene (1400bp) amplification followed by sequencing the product by send it directly for DNA Sanger Sequencing to Macrogen Company / Soul, Korea, data were analyzed and edit using Geneious Program and the edited sequence were compare with data base using BLAST (Basic Local Alignment Search Tool) to find the closed relation with submitted sequences, the second method is Real-Time Polymerase Chain Reaction by recA gene (385 bp fragment) amplification. The VITEK 2 System identify all the B.cepacia isolates with confidence values (97-99) %, 16S rRNA gene amplification and sequencing results confirm the identification with percentages of identification ranging from (96-99) %, after sequencing analysis, one of the B.cepacia isolate had been submitted in Gen Bank ((National Centre Biotechnology Information NCBI) under the accession number (MF678807). These results highlight the advantage of using these PCR assay to detect B. cepacia from different clinical sources that confirm the identification of isolates which may be misidentified when biochemically tested.Keywords: Burkholderia cepacia, Molecular identification, PCR, 16S rRNA gene sequencing, Real-Time PCR, recA gene.